Building A High-Performance Culture: The Balance Between Competition And Career Support - Ahmad Farabi; Budi Syamtoro; Hamida Hunein (Jurnal Bisnis dan Manajemen, 2026)
This study examines how competition and career support influence the development of a high-performance culture within organizations. Design methodologyA quantitative approach was employed, using survey data from 111 employees. Multiple regression analysis tested the direct effects of competition and career support on high-performance culture, with validity and reliability confirmed via Pearson correlation and Cronbach’s Alpha. Findings –Both competition and career support significantly and positively affect high-performance culture. Career support showed a stronger influence than competition. The combined model explained 54.8% of the variance, demonstrating strong predictive power. Research limitations/implications the cross-sectional design limits causal inference. Future studies should adopt longitudinal designs, include objective performance metrics, and explore moderating variables such as industry type and leadership style. Practical implications Organizations should integrate competitive performance mechanisms with structured career development programs. Leaders must balance challenge with support to foster a sustainable high-performance environment. Social implications  Cultivating performance cultures that value both achievement and employee growth contributes to professional development, job satisfaction, and organizational sustainability. Originality/value This research provides empirical validation of competition and career support as dual drivers of high-performance culture, offering a balanced framework for organizational development.